Ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid loaded onto fluorescent mesoporous silica nanoparticles for the location and therapy of nasopharyngeal carcinoma. Issue 5 (21st January 2021) - Liu, Yuke; Zhou, Le; Tan, Jing; Xu, Weiqiang; Huang, Guoliang; Ding, Jie
Abstract : Mesoporous silica nanoparticles promote ent -11α-hydroxy-15-oxo-kaur-16-en-19-oic acid, extracted from the Chinese herbal medicine Pteris semipinnata L., to make more important impact in the treatment of low-differentiated nasopharyngeal carcinoma. Abstract : Ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid (5F) is a diterpenoid that is isolated and purified from the Chinese herbal medicine Pteris semipinnata L., and is known to exert antitumour activity in several kinds of malignant cancer cells by leading cancer cells to apoptosis. However, the antitumour effect of 5F in vivo is rarely reported due to the complexity of the physiological environment and limitations of 5F as a small anticancer drug. In the present study, we utilized FITC-doped nanoparticles for the accumulation and delivery of 5F in nasopharyngeal carcinoma CNE2 tumours transplanted in nude mice by the enhanced permeation and retention (EPR) effect. In vivo studies demonstrated that nanoparticles could efficiently deliver 5F in CNE2 transplanted tumours, and the tumour growth was effectively inhibited by the drug-loaded nanoparticles with minimal side effects. The study indicated the benefits of combining well-studied nanoparticles with traditional herbal medicine treatment and establishes a delivery platform for 5F chemotherapy.